Three Functions of Political Parties in Representative Democracies - Wolkenstein, Fabio (Momentum Quarterly, 2013)
Political parties and democracy are often said to have an uneasy alliance. This article reconstructs three core functions of parties in Western representative democracies, drawing on normative democratic theory. It is argued that parties serve aggregative, motivational and deliberative functions in representative democracies. Recent findings and debates in party scholarship suggest that parties gradually lose their capacity to serve these functions because of organisational changes parties have undergone in the last three decades.